Hypothalamic KNDy neuron expression in streptozotocin-induced diabetic female rats. Issue 1 (23rd February 2022) - Enomoto, Hiroyuki; Iwata, Kinuyo; Matsumoto, Keisuke; Otsuka, Mai; Morita, Akio; Ozawa, Hitoshi
Abstract : Kisspeptin neurons, i.e. KNDy neurons, in the arcuate nucleus (ARC) coexpress neurokinin B and dynorphin and regulate gonadotropin-releasing hormone/luteinizing hormone (LH) pulses. Because it remains unclear whether these neurons are associated with reproductive dysfunction in diabetic females, we examined the expression of KNDy neurons detected by histochemistry in streptozotocin (STZ)-induced diabetic female rats 8 weeks after STZ injection. We also evaluated relevant metabolic parameters – glucose, 3-hydroxybutyrate, and non-esterified fatty acids – as indicators of diabetes progression. Severe diabetes with hyperglycemia and severe ketosis suppressed the mRNA expression of KNDy neurons, resulting in low plasma LH levels and persistent diestrus. In moderate diabetes with hyperglycemia and moderate ketosis, kisspeptin-immunoreactive cells and plasma LH levels were decreased, while the mRNA expression of KNDy neurons remained unchanged. Mild diabetes with hyperglycemia and slight ketosis did not affect KNDy neurons and plasma LH levels. The number of KNDy cells was strongly and negatively correlated with plasma 3-hydroxybutyrate levels. The vaginal smear analysis showed unclear proestrus in diabetic rats 3–5 days after STZ injection, and the mRNA expression of kisspeptin in the ARC was decreased 2 weeks after STZ injection in severely diabetic rats. Kisspeptin neurons in the anteroventral periventricular nucleus (AVPV), which induce an LH surge, were unaffected at 2 and 8 weeks after STZ injection regardless of the diabetes severity. These results suggest that diabetes mellitus progression in females may negatively affect ARC kisspeptin neurons but not AVPV kisspeptin neurons, implicating a potential role of ARC kisspeptin neurons in menstrual disorder and infertility.